Evaluasi Penggunaan Quizizz Untuk Meningkatkan Motivasi Belajar Peserta Didik - Yohanes Dwi Saputro; Muji Lestari (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
Success in learning is evidenced by student achievement that appears both during learning and after learning. Students who excel certainly have the motivation to be the best in their class, this factor underlies researchers to conduct research related to aspects of competition in encouraging students to excel more in competition within the class. The method used by researchers uses Project Based Learning with the help of the Quizizz application. The facilities provided by the Quizizz application are believed to be able to encourage students to compete and excel. With the Quizizz application students can see firsthand the results of their work in answering questions and there are also other facilities such as the power to add points if they answer correctly, so that points will be counted 2 times as much as usual. Gibbs Reflective Learning Cycle used in evaluating the learning process Unlike previous studies, this study applies 360-degree assessment techniques derived from teachers and learners to evaluate the performance of the use of technology in the learning process.